Swot Analysis PT. Bumi Raflesia Indah In Distribution Of Corporate Social Responsibility Assistance - Panco Agus Marmo; Evi Lorita; Antonio Imanda (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the results of the SWOT analysis of PT. Bumi Raflesia Indah in Distributing Corporate Social Responsibility Assistance. This study used descriptive qualitative method. Collecting data using observation, interview, and documentation techniques. Based on the research results, it is known that: (1) Strengths owned by PT. Bumi Raflesia Indah in Distributing Corporate Social Responsibility Assistance are: (a) Availability of a CSR fund budget of 5% of the company's profits or profits each year, (b) Availability of technology that can be used by companies and the community in distributing CSR funds in the form of motorized vehicles four wheels such as trucks and pickups, (c) Human resources who participate in helping the distribution of CSR assistance in the company are HRD employees who are assisted by security guards and other employees appointed by the leadership. (2) Weaknesses owned by PT. Bumi Raflesia Indah in Distributing Corporate Social Responsibility Assistance, the main things are: (a) The minimum budget issued by the company, (b) The location is far away and the terrain is difficult (slippery and steep). (3) Opportunities owned by PT. Bumi Raflesia Indah in Distributing Corporate Social Responsibility Assistance are: (a) There is a company policy regarding the approval of CSR assistance. The policy was made by the leadership as a form of corporate social responsibility to the community and the surrounding environment, (b) There was a positive response from the community. (4) Threats owned by PT. Bumi Raflesia Indah in Distributing Corporate Social Responsibility Aid are: (a) The distribution of aid is hampered. (b) The safety of the team in distributing aid is threatened. This is because such conditions can threaten the safety of the team or employees when distributing CSR assistance.